Analisis Kepemimpinan dan Kompensasi Terhadap Disiplin Kerja Karyawan PT. Panen Lestari Indonesia Cabang Kota Medan - Maulidina Fidhia; Muhammad Yalzamul Insan (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The purpose of this study is to find out whether leadership and compensation have a significant effect on employee work discipline. This study uses a quantitative approach. This study involved a sample with a total of 58 respondents. Data were collected using primary data by distributing questionnaires. Data analysis uses an associative research method using SPSS 19. Multiple linear regression analysis is used in this study. The findings of the study stated that leadership had a positive and partially significant influence on employee work discipline at PT. Panen Lestari Indonesia Medan City Branch. The findings of the compensation variable test show that at PT. Panen Lestari Indonesia Medan City Branch, compensation has a significant and partially positive effect on employee work discipline. This means that leadership and compensation simultaneously have a significant effect on employee performance at PT. Panen Lestari Indonesia Medan City Branch